Logics in artificial intelligence : 15th European conference, JELIA 2016, Larnaca, Cyprus, November 9-11, 2016, proceedings /: 15th European conference, JELIA 2016, Larnaca, Cyprus, November 9-11, 2016, proceedings. (2016) - Unknown
No abstract available